2003
DOI: 10.1046/j.1420-9101.2003.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture for normal and novel host-plant use in two local populations of the herbivorous ladybird beetle, Epilachna pustulosa

Abstract: Trade-offs in host-plant use are thought to promote the evolution of host specificity. However, usually either positive or no genetic correlations have been found. Whereas factors enhancing variation in overall viability have been claimed to mask negative genetic correlations, alternative hypotheses emphasize the sequential changes in genetic correlation in the course of hostrange evolution. In this study, the genetic architectures of performances on different hosts were compared in two populations of the herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 65 publications
1
37
0
1
Order By: Relevance
“…Studies using environmentÂgenetic interactions (GÂE) only were not included as a significant GÂE interaction does not necessarily indicate genetic trade-off (see Falconer and McKay, 1996;Roff, 1997 on p. 206). Recent examples of studies that found significant GÂE interactions but no evidence for a negative genetic correlation in performance are for instance Peppe and Lomoˆnaco (2003) and Ueno et al (2003). We also noted whether the arthropod species is able to reproduce asexually (including cyclic parthenogenesis like aphids and gynogenetic reproduction like in Alsophila pometaria) or is obligate sexually.…”
Section: Methodsmentioning
confidence: 70%
“…Studies using environmentÂgenetic interactions (GÂE) only were not included as a significant GÂE interaction does not necessarily indicate genetic trade-off (see Falconer and McKay, 1996;Roff, 1997 on p. 206). Recent examples of studies that found significant GÂE interactions but no evidence for a negative genetic correlation in performance are for instance Peppe and Lomoˆnaco (2003) and Ueno et al (2003). We also noted whether the arthropod species is able to reproduce asexually (including cyclic parthenogenesis like aphids and gynogenetic reproduction like in Alsophila pometaria) or is obligate sexually.…”
Section: Methodsmentioning
confidence: 70%
“…3 and 4; Table 3), because a previous study revealed that at least F 1 hybrid larvae between populations on M. micrantha and L. lavandulifolia are as viable as their parents on both host plants (Matsubayashi et al 2011). In addition, a series of previous studies dealing with congeneric phytophagous ladybird beetles detected no evidence for the genetic trade-offs investigated in terms of signiÞcant negative genetic correlations, at least regarding the ability of larvae to develop on hosts from different plant families (Ueno et al 1999(Ueno et al , 2003; although the species treated in these studies were referred to as genus Epilachna, they are now placed in Henosepilachna). On the other hand, alternative theoretical models have predicted that panmictic generalist insect populations can become specialized, even in the absence of genetic trade-offs, on the host plant on which the majority of the population develops (Fry 1996), or on the main host of the population in a heterogeneous habitat (Kawecki et al 1997).…”
Section: Discussionmentioning
confidence: 86%
“…One potential source for adaptive differentiation between species is in how they express trade-offs between different correlates of fitness. Standard errors on all quantitative genetic estimates were obtained by jackknifing over families (Efron & Tibshirani, 1993;Ueno et al, 2001Ueno et al, , 2003. We therefore looked for genetically based trade-offs in performance in two places, among pairs of hosts for a given dependent variable (weight, duration, and DGR), and between pairs of dependent variables for a given host, by examining and comparing the corresponding correlation or G -matrices of the two species.…”
Section: Methodsmentioning
confidence: 99%